O‐fucosylation of CCN1 is required for its secretion. Issue 21 (28th September 2015) - Niwa, Yuki; Suzuki, Takehiro; Dohmae, Naoshi; Simizu, Siro
Abstract : The matricellular protein CCN1, also known as Cyr61, is a secreted ligand and has numerous functions. Human CCN1 contains one predicted O ‐fucosylation site in the thrombospondin type‐1 repeat (TSR1) domain at Thr 242 . In this report, we demonstrated that CCN1 is O ‐fucosylated at Thr 242 using mass spectrometry. Deficiency of O ‐fucosylation resulted in the decrement of the cell surface localization and the secretion of CCN1. Furthermore, knockdown of protein O ‐fucosyltransferase 2, which modifies a specific Ser/Thr residue in the TSR1 domain, decreased secreted levels of CCN1. These results demonstrated that O ‐fucosylation of CCN1 at Thr 242 regulates its secretion. Abstract : Human CCN1 is O ‐fucosylated at Thr 242 . O ‐fucosylation‐defective mutant of CCN1 decreased the secretion level. Pofut2‐mediated O ‐fucosylation is required for the secretion of CCN1. Secretion of CCN1 is regulated by O ‐fucosylation.